Optimal Quantitave and Distributive Analysis of Thermal Pollution due to Heated Water Released to Rivers - H.Al-Suhaili, Rafa; J.Al-Mosewi, Tariq (Iraqi Journal of Chemical and Petroleum Engineering, 2008)
To reduce the effects of discharging heated water disposed into a river flow by a single thermal source, two parameters were changed to get the minimum effect using optimization. The first parameter is to distribute the total flow of the heated water between two disposal points (double source) instead of one and the second is to change the distance between these two points. In order to achieve the solution, a two dimensional numerical model was developed to simulate and predict the changes in temperature distribution in the river due to disposal of the heated water using these two points of disposal. MATLAB-7 software was used to build a program that could solve the governing partial equations of thermal pollution in rivers by using the finite difference technique. The distribution of temperature in the river was presented by using the SURFER software that was used to draw the temperature contour lines and computing the areas of critical temperature (The area where the temperature exceed a certain selected value, which is believed to be critical for aquatic life). The optimum case was that which gave the minimum critical area. The decision variables are the subdivided flow of the two disposal points, and the distance between these two points. The result had indicated that the optimum case can be achieved when the flow of first point was 0.1 from the total flow of heated water and the second was 0.9 from this total flow. The optimal distance between the two points was found to be 30 m.